Metabolo-epigenetic interplay provides targeted nutritional interventions in chronic diseases and ageing - Gómez de Cedrón, Marta; Moreno Palomares, Rocío; Ramírez de Molina, Ana (Frontiers in Oncology, 2023)
Epigenetic modifications are chemical modifications that affect gene expression without altering DNA sequences. In particular, epigenetic chemical modifications can occur on histone proteins -mainly acetylation, methylation-, and on DNA and RNA molecules -mainly methylation-. Additional mechanisms, such as RNA-mediated regulation of gene expression and determinants of the genomic architecture can also affect gene expression. Importantly, depending on the cellular context and environment, epigenetic processes can drive developmental programs as well as functional plasticity. However, misbalanced epigenetic regulation can result in disease, particularly in the context of metabolic diseases, cancer, and ageing. Non-communicable chronic diseases (NCCD) and ageing share common features including altered metabolism, systemic meta-inflammation, dysfunctional immune system responses, and oxidative stress, among others. In this scenario, unbalanced diets, such as high sugar and high saturated fatty acids consumption, together with sedentary habits, are risk factors implicated in the development of NCCD and premature ageing. The nutritional and metabolic status of individuals interact with epigenetics at different levels. Thus, it is crucial to understand how we can modulate epigenetic marks through both lifestyle habits and targeted clinical interventions -including fasting mimicking diets, nutraceuticals, and bioactive compounds- which will contribute to restore the metabolic homeostasis in NCCD. Here, we first describe key metabolites from cellular metabolic pathways used as substrates to “write” the epigenetic marks; and cofactors that modulate the activity of the epigenetic enzymes; then, we briefly show how metabolic and epigenetic imbalances may result in disease; and, finally, we show several examples of nutritional interventions - diet based interventions, bioactive compounds, and nutraceuticals- and exercise to counteract epigenetic alterations.